2022
DOI: 10.1136/bmjopen-2022-061025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of healthcare system transformations spurred by the COVID-19 pandemic on management of stroke and STEMI: a registry-based cohort study in France

Abstract: ObjectiveTo assess the impact of changes in use of care and implementation of hospital reorganisations spurred by the COVID-19 pandemic (first wave) on the acute management times of patients who had a stroke and ST-segment elevation myocardial infarction (STEMI).DesignTwo cohorts of patients who had an STEMI and stroke in the Aquitaine Cardio-Neuro-Vascular (CNV) registry.Setting6 emergency medical services, 30 emergency units (EUs), 14 hospitalisation units and 11 cathlabs in the Aquitaine region.Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 45 publications
(71 reference statements)
2
13
0
Order By: Relevance
“…While the COVID-19 pandemic crisis is nearly resolved, our findings remain valuable for health institutions and professionals to prepare for future health crises. The structured emergency pathway for strokes and STEMI patients and hospital reorganisations ensured sustained care quality 12. In our study, the COVID-19 crisis did not have any differential impact on social health inequalities, suggesting a good resilience of the French healthcare network.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…While the COVID-19 pandemic crisis is nearly resolved, our findings remain valuable for health institutions and professionals to prepare for future health crises. The structured emergency pathway for strokes and STEMI patients and hospital reorganisations ensured sustained care quality 12. In our study, the COVID-19 crisis did not have any differential impact on social health inequalities, suggesting a good resilience of the French healthcare network.…”
Section: Discussionmentioning
confidence: 55%
“…Guidelines and national stroke and STEMI improvement programmes recommend the implementation of such structured pathways, which include close collaborations between healthcare professionals and patient orientation to the EMS system and specialised technical platforms. A study of the impacts of changes in the use of care and implementation of hospital reorganisation spurred by the COVID-19 pandemic on acute management times for stroke and STEMI revealed no deep alteration of the emergency pathway construct 12. Socially and/or clinically vulnerable populations have also benefited from the resilience of the STEMI and stroke pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Management did not differ for STEMI patients and the delays in stroke care could not be definitively determined. 1 Inpatient admissions to a United States Veterans Affairs stroke service went unchanged but 1 medical center reported fewer telestroke consultations during the first and second waves of coronavirus disease 2019 public health mandates. 2 A single-center study in China reported that half as many patients with large vessel occlusion were treated during the pandemic, plus a 2-fold increase in door-to-puncture times, longer hospital stays, and greater hospitalization costs.…”
Section: Research Examining Existing Policiesmentioning
confidence: 99%